Relationship between social indicators and food insecurity: a systematic review - Juliana de Bem Lignani; Poliana de Araujo Palmeira; Marina Maria Leite Antunes; Rosana Salles-Costa (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2020)
ABSTRACT: Introduction: The relationships between the social indicators (SIs) that determine food insecurity (FI) have not been described yet. This systematic review aims to identify which SIs are associated with FI in Brazilian households and how these relationships are explained. Methods: The research protocol was registered on the International Prospective Register of Systematic Reviews (PROSPERO - CRD42018106527). Three independent researchers performed the search in the Latin American and Caribbean Health Sciences Literature (LILACS) and National Library of Medicine (PubMed) databases (June/2018). The study included articles that used the Brazilian Household Food Insecurity Measurement Scale (Escala Brasileira de Insegurança Alimentar - EBIA) to assess FI and that evaluated the association between SIs and FI. Results: We included 18 articles in this review. The Kappa concordance index between the researchers was 0.72 (95%CI 0.42 - 1.00). Most articles were cross-sectional and used multivariate regression for the statistical analysis. At least one income-related SI had a significant association with FI, and, in most studies, they presented the highest values of association measures. We organized the authors' explanation about the relationships between SIs and FI in a conceptual model. The study identified three possible justifications for the association between SIs and FI: direct relationship, relationship mediated by income, or relationship mediated by another SI and income. Conclusion: Income assumed a central role in the mediation between several SIs and FI. However, the analysis methods of the studies did not allow us to investigate this mediation. Therefore, improving data analysis to isolate and understand the effect of SIs on FI is still necessary.